2018
DOI: 10.1111/phn.12397
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from using an audience response system in a community setting for research data collection

Abstract: The lessons learned here can help community-academic research partnerships identify the best circumstances in which to use ARS for data collection and practical steps to aid in its success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Data collection were led by the FAITH Network Research Advocates using an Audience Response System (ARS) (Bryant‐Moore, et al., 2018 ; Yeary et al., 2016 ) from participants recruited by the first cohort of advocates in five places of worship (10 participants per place of worship for with a total of 50 participants). Participants were welcomed as they entered the facility.…”
Section: Methodsmentioning
confidence: 99%
“…Data collection were led by the FAITH Network Research Advocates using an Audience Response System (ARS) (Bryant‐Moore, et al., 2018 ; Yeary et al., 2016 ) from participants recruited by the first cohort of advocates in five places of worship (10 participants per place of worship for with a total of 50 participants). Participants were welcomed as they entered the facility.…”
Section: Methodsmentioning
confidence: 99%
“…As evidence, a 2016 systematic review of church-based mental health initiatives found only five articles out of 627 where researchers implemented and empirically evaluated faith-based mental health interventions for African Americans (Hays & Aranda, 2016). Recent work implementing a group-based mental health and behavioral activation intervention in historically Black churches found that the initiative was negatively impacted by low intervention adherence, due to a high prevalence of mental health stigma within the community (Bryant-Moore et al, 2019). This finding was echoed in a 2021 survey administered at a church-sponsored mental health awareness event, which reported that the most significant barrier to care-seeking is the fear of "being labeled" (Ormond et al, 2021).…”
mentioning
confidence: 99%
“…Effectiveness of and engagement in health interventions set in the physical world, compared to virtual settings, may also be diminished by church member privacy and confidentiality concerns. Such concerns may be even more necessary to consider when implementing health initiatives that focus on sensitive or stigmatized topics like mental health (Bryant-Moore et al, 2019). Together, these barriers significantly limit the ability of in-person-only programs to sustainably and effectively address church member mental wellness.…”
mentioning
confidence: 99%